Der Einfluss des Kapseldefektes als Risikofaktor für die Rezidivbildung beim pleomorphen Adenom der Glandula parotidea - Buchta, Peter; Thimsen, Vivian; Iro, Ann-Kristin; Agaimy, Abbas; Iro, Heinrich; Mantsopoulos, Konstantinos (Laryngo-Rhino-Otologie, 2021)
Objective Aim of this study was to enlighten various aspects of the capsular defect of a pleomorphic adenoma and to analyze its influence on recurrence rate with the help of our data and the relevant literature. Material and Methods The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were evaluated retrospectively. The histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. The records of the cases with a capsular defect were examined for information on age, gender, type of surgery and surgical outcome. Results A total of 845 patients were included in the primary group.7 (0.8%) recurrences were detected, all of these were resected without a capsular rupture. Positive margins were found in 37 cases (4.4%). In 13/37 cases the capsular defect was detected intraoperatively, whereas the defect was only identified histopathologically in 24 of the 37 cases. In the group of the intraoperative capsular opening, with a median follow-up of 62 months, the sonographic examination suspected a unilocular recurrence of the pleomorphic adenoma in two cases. Conclusion The intraoperative capsule opening does not inevitably seem to lead to a pre-programmed recurrence.
CRIS-Team Scopus Importer:2021-07-09
Keywords: capsule; capsule opening; parotid gland; pleomorphic adenoma; recurrence; recurrence rate